Advance Planning, Programming and Production Control as key Activities Now the Environmental Education (Revista Brasileira Multidisciplinar, 2010)
This work addresses the evolution of Planning, Programming and Control of Production (PPCP) as essential activities of the company towards the insertion of environmental education. The approach is based on an exploratory research and a critical bibliographic revision. Two main objectives were established: i) a new way of production organization, by considering cleaner production from company utilities to production capacity, technology and outsourcing and ii) infrastructure changes related to market attendance and environmental education dissemination. Needs that arise can be grouped as follows: utilities adequacy, cleaner technologies and ecochains implementation; instruction and dissemination of environmental education; and necessity of the adoption of new paradigms.
Keywords: Cleaner Production; Lean Production; Planning; Programming and Control with environmental education.